2015
DOI: 10.1155/2015/494383
|View full text |Cite
|
Sign up to set email alerts
|

Carcinosarcoma of the Thyroid Gland

Abstract: Introduction. Surgeon has significant role in the management of such rare and controversial clinical entities related to thyroid gland. In this case report we have presented an elderly patient with rapid enlargement in thyroid that was related to carcinosarcoma. Case Presentation. A 60-year-old lady was presented with rapid enlargement of the thyroid gland. A fine needle aspiration of the nodule in right lobe was performed several weeks before presentation to our clinic. End diagnosis was a papillary carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
(3 reference statements)
1
0
0
Order By: Relevance
“…The results suggest that these tumours are a very aggressive malignancy in dogs. While also rare in humans, the outcomes described here are similar to outcomes in humans with thyroid carcinosarcomas where the survival is typically only a few months (al‐Sobhi et al., 1997 , Yang et al., 2018 , Agrawal et al., 2013 , Ekici et al., 2015 ). In one study of 17 reported humans with thyroid carcinosarcomas, the reported median survival time was 5 months (al‐Sobhi et al., 1997 ).…”
Section: Discussionsupporting
confidence: 71%
“…The results suggest that these tumours are a very aggressive malignancy in dogs. While also rare in humans, the outcomes described here are similar to outcomes in humans with thyroid carcinosarcomas where the survival is typically only a few months (al‐Sobhi et al., 1997 , Yang et al., 2018 , Agrawal et al., 2013 , Ekici et al., 2015 ). In one study of 17 reported humans with thyroid carcinosarcomas, the reported median survival time was 5 months (al‐Sobhi et al., 1997 ).…”
Section: Discussionsupporting
confidence: 71%